Chromosome-level reference genome assembly provides insights into the evolution of Pennisetum alopecuroides - Teng, Ke; Guo, Qiang; Liu, Lingyun; Guo, Yidi; Xu, Yue; Hou, Xincun; Teng, Wenjun; Zhang, Hui; Zhao, Chunqiao; Yue, Yuesen; Wen, Haifeng; Wu, Juying; et al. (Frontiers in Plant Science, 2023)
Pennisetum alopecuroides is an important forage grass resource, which plays a vital role in ecological environment improvement. Therefore, the acquisition of P. alopecuroides genome resources are conducive to the study of the adaptability of Pennisetum species in ecological remediation and forage breeding development. Here, we assembled a P. alopecuroides cv. "Liqiu" genome at the chromosomal level with a size of approximately 845.71Mb, contig N50 of 84.83Mb, and genome integrity of 99.13% as assessed by CEGMA. A total of 833.41Mb sequences were mounted on 9 chromosomes by Hi-C technology. 60.66 % of the repetitive sequences and 34,312 genes were predicted. Genomic evolution analysis showed that P. alopecuroides cv."Liqiu" was isolated from Setaria 7.53-13.80 million years ago, and from Cenchrus 5.33-8.99 million years ago, respectively. Whole genome event analysis showed that P. alopecuroides cv. "Liqiu" underwent two whole genome duplication (WGD) events in the evolution process, and the duplication events occurred at a similar time to that of O. sativa and S. viridis. The completion of genome sequencing of P. alopecuroides cv."Liqiu" provides data support for mining high-quality genetic resources of P.alopecuroides, and provides theoretical basis for the origin and evolutionary characteristics of Pennisetum.